immuneACCESS
DOI: 10.21417/b72d1q
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TET2 promotes the therapeutic efficacy of CD19-targeted T cells

Abstract: Cancer immunotherapy based on genetically redirecting T-cells has been used successfully to treat B-cell malignancies [1][2][3] . In this strategy, the T-cell genome is modified by integration of viral vectors or transposons encoding chimeric antigen receptors (CARs) that direct tumor cell killing. However, this approach is often limited by the extent of expansion and persistence of CAR Tcells 4,5 . Here we report mechanistic insights from studies of a chronic lymphocytic leukemia (CLL) patient treated with CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Additionally, further analysis of observations in patients with a notable expansion and/or persistence of the CAR T cells suggest a role for targeted genomic integration of the CAR construct to enhance persistence. For example, the anecdotal experience of clonal expansion in a patient with CLL revealed that TET2 disruption results in alterations in CAR T cell biology, leading to enhanced potency and a central memory phenotype 91 . Similarly, specific integration of the CAR gene into the TCRα constant (TRAC) locus of the T cell genome using CRISPR-Cas9 editing machineries results in better antitumour responses than those observed with conventionally transduced CAR T cells in preclinical models 92 .…”
Section: Nature Reviews | Clinical Oncologymentioning
confidence: 99%
“…Additionally, further analysis of observations in patients with a notable expansion and/or persistence of the CAR T cells suggest a role for targeted genomic integration of the CAR construct to enhance persistence. For example, the anecdotal experience of clonal expansion in a patient with CLL revealed that TET2 disruption results in alterations in CAR T cell biology, leading to enhanced potency and a central memory phenotype 91 . Similarly, specific integration of the CAR gene into the TCRα constant (TRAC) locus of the T cell genome using CRISPR-Cas9 editing machineries results in better antitumour responses than those observed with conventionally transduced CAR T cells in preclinical models 92 .…”
Section: Nature Reviews | Clinical Oncologymentioning
confidence: 99%
“…Strategies to enhance CAR T cell persistence, memory or effector cell activity, as discussed in this review: (a) Cytokine stimulation during ex vivo CAR T cell generation; (b) small molecule inhibitors that activate transcription or metabolic transformation; (c) membrane expression of homeostatic cytokines, for example, mIL ‐15; (d) immune checkpoint blockade (e.g. with anti‐ PD 1 mA b); (e) knockout of pro‐exhaustion demethylase tet2 ; (f) enforced expression of micro RNA to enhance persistence and anti‐tumor activity, for example, miR‐155 or miR‐143; (g) detuning CD 3ζ activation by reducing ITAM number; or (h) choice of costimulator domain to enhance memory or persistence appropriate to the subtype of cancer . [The color version of this figure can be viewed at www.wileyonlinelibrary.com/journal/icb]…”
Section: Subsets Of Memory Cellsmentioning
confidence: 99%
“…Methylation of DNA can alter the transcription levels of a variety of immune‐associated genes, resulting in changes in T cell differentiation and activity. Disruption of the tet2 gene improves T cell proliferation and memory differentiation . In particular, a recent study found that in one CLL patient in remission, CAR T cells had preferentially expanded from a single clone that harbored one allele with an inborn loss of tet2 function, while the second allele had been mutated by the transgene insertion .…”
Section: Strategies To Enhance Car T Cell Persistence and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Future directions to minimize tumor escape and increase effectiveness of CAR-T cell products include combinations [123] and modulation of the immunosuppressive tumor microenvironment through checkpoint inhibitors [124], combinations with immunomodulatory drugs [125], targeting the epigenome [126,127], incorporating novel costimulation [128] and dual targeting antigen [129]. In an attempt to improve safety and potency, advances in of CRISPR/Cas9 [130] and TALEN-mediated [131] genome-editing approaches for the large-scale manufacturing of 'off-the-shelf' CAR-T cells are outperforming conventionally transduction methods (NCT03399448).…”
Section: Chimeric Antigen Receptor T Cell Therapymentioning
confidence: 99%